KELAYAKAN PENGGUNAAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS MULTIMEDIA INTERAKTIF SISWA KELAS X (Edu Geography, 2016)
This study aims to find out: (1) To determine the feasibility of the use of Geographic-Based Learning Media Interactive Multimedia Power Exogenous material in class X SMA Banyumas 2nd semester of the school year 2013/2014, (2) To determine the effectiveness of instructional media and student interest towards learning when using this instructional media. Samples were students of class X IIS 2 and X IIS 4 SMA Banyumas, determined using simple random sampling technique. Data collection techniques with documentation, questionnaires, and tests. Data analysis technique used is descriptive and percentage gain test. Results of the study are: (1) Summary of the feasibility study media with criteria 90.40% "Very Decent", (2) The results of the analysis of questionnaire responses and improved student learning outcomes of this study indicate that the media effectively, as well as students interested in learning Geography Power Exogenous material. It can be concluded that the Geography-Based Learning Media Interactive Multimedia Power Exogenous material fit for use in SMA Negeri Banyumas, effective learning media, and students interested in learning when using this media.